2017
DOI: 10.1128/aac.01753-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Susceptibility Profiles of 12 Antifungal Drugs against 55 Trichophyton schoenleinii Isolates from Tinea Capitis Favosa Patients in Iran, Turkey, and China

Abstract: Trichophyton schoenleinii is an anthropophilic dermatophyte mainly causing tinea favosa of the scalp in certain regions of the world, especially Africa and Asia. We investigated the in vitro susceptibilities of 55 T. schoenleinii isolates collected over the last 30 years from Iran, Turkey, and China to 12 antifungals using the CLSI broth microdilution method. Our results revealed that terbinafine and ketoconazole were the most potent antifungal agents among those tested, independently of the geographic regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
4
19
1
Order By: Relevance
“…A review of previously reported geometric means (GMs), MIC 50 , MIC 90 and MIC ranges of T schoenleinii are listed in Table . GM MICs for all isolates used in this study were, TBF 0.03, MCZ 0.196, KTZ 0.272, ITZ 0.376, GRF 0.722, NYT 3.281 and FLZ 5.087 μg/mL. TBF is the most potent agent for all isolates.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…A review of previously reported geometric means (GMs), MIC 50 , MIC 90 and MIC ranges of T schoenleinii are listed in Table . GM MICs for all isolates used in this study were, TBF 0.03, MCZ 0.196, KTZ 0.272, ITZ 0.376, GRF 0.722, NYT 3.281 and FLZ 5.087 μg/mL. TBF is the most potent agent for all isolates.…”
Section: Resultssupporting
confidence: 55%
“…Our cases were difficult to diagnose and some were misdiagnosed for decades. No studies of molecular epidemiology have been performed to monitor T schoenleinii and very limited data are available on its susceptibility to currently used antifungal agents . Questions of public health and scientific interest therefore remain, for example on the species origin, distribution profiles, and antifungal resistance.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Deng et al 7 stated that terbinafine and ketoconazole were the most recommended for T. schoenleinii among 12 systemic and topical antifungal drugs in 2007. However, there are not a few cases of favus treated with griseofulvin even nowadays.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro efficacy of echinocandin drugs against dermatophytes was firstly evaluated by Bao et al (2013) , who demonstrated that caspofungin and micafungin did not entirely inhibit growth, but exhibit good in vitro antifungal activity to dermatophytes. Recent studies also showed that anidulafungin has potent in vitro activity against dermatophytes although the relevance for clinical efficacy has not yet been established ( Badali et al, 2015 ; Baghi et al, 2016 ; Deng et al, 2017 ). The absence of in vivo studies of echinocandins efficacy limits its use for treatment of dermatophytosis, which may underlie the absence of resistant dermatophyte strains described to date.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%